2015
DOI: 10.1038/ja.2015.126
|View full text |Cite
|
Sign up to set email alerts
|

Maniwamycins: new quorum-sensing inhibitors against Chromobacterium violaceum CV026 were isolated from Streptomyces sp. TOHO-M025

Abstract: Quorum sensing is an important microbial signaling system that controls the expression of many virulence genes. Maniwamycins C-F, new compounds and quorum-sensing inhibitors, were isolated from the culture broth of Streptomyces sp. TOHO-M025 using a silica gel column and preparative HPLC. The structures of maniwamycins were elucidated by spectroscopic analyses, including NMR. The compounds each have an azoxy moiety. All maniwamycins inhibited violacein synthesis, which is controlled by quorum sensing, in Chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 27 publications
3
45
0
Order By: Relevance
“…The unremitting discovery of antibiotics showed a promising prospect for the bacterial infections, but also resulted in the serious resistance of antibiotics. Bacteria have evolved a variety of resistance mechanisms [1,2]. Quorum sensing (QS) is the regulation of gene expression in response to fluctuations in cell-population density among diverse bacterial species [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unremitting discovery of antibiotics showed a promising prospect for the bacterial infections, but also resulted in the serious resistance of antibiotics. Bacteria have evolved a variety of resistance mechanisms [1,2]. Quorum sensing (QS) is the regulation of gene expression in response to fluctuations in cell-population density among diverse bacterial species [3].…”
Section: Introductionmentioning
confidence: 99%
“…The EtOAc extract of the fermentation broth of this fungus showed obvious QS inhibitory activity against Chromobacterium violaceum CV026. Subsequent chemical investigation on the EtOAc extract of the fermentation broth had led to the isolation of five new compounds, named altertoxins VIII-XII (1)(2)(3)(4)(5), as well as a known one, cladosporol I (6) [10] (Figure 1). All of the new compounds showed obvious QS inhibitory activities.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, natural resources from plants and microorganisms have received attention as sources of bacterial QS inhibitors26. Known compounds that have been demonstrated to inhibit the bacterial QS system include p -coumaric acid from garlic extract27, methyl eugenol from Cuminum cyminum 28, baicalein from Scutellaria baicalensis 29, curcumin from Curcuma longa 30, maniwamycins from Streptomyces sp 31,. unidentified secondary metabolites from marine Streptomyces 32, furanosesterterpenes from the marine sponge Ircinia felix 33, sesqui- and triterpenoids from the liverwort Lepidozia chordulifera 34, and unidentified components from edible mushrooms3536.…”
mentioning
confidence: 99%
“…Antibiotic compound that produced by S. prasinopilosus was identified as maniwamycins [37], it antibiotic were found to be azoxy substances and showed broad antifungal spectra. Fukumoto [38] found that maniwamycins is able to inhibit violacein synthesis, which is controlled by quorum sensing in Chromobacterium violaceum. Similarly, isolate S. prasinopilosus PN-TN2 also interferes with the quorum sensing process in S. marcescens so that although the growth of bacteria was not inhibited but they cannot synthesize the red pigment (prodigiosin) which is an important virulence factor and produced by quorum sensing process.…”
Section: Molecular Identification Of Potential Actinomycetesmentioning
confidence: 99%